Prophylactic Insertion of Large Bore Peripheral Intravenous Catheters in Maternity Patients for Postpartum Haemorrhage: A Cohort Study. Issue 3 (September 2019) - Webster, J.; Larsen, E.; Booker, C.; Laws, J.; Marsh, N.
Abstract : ( Aust N Z J Obstet Gynaecol . 2018;58:548–552) In Australia, most women undergoing labor and vaginal delivery receive a peripheral intravenous catheter (PIVC) for any needed IV fluids, blood products or medications. While the smallest gauge catheter necessary is recommended by guidelines for intravenous access, many women receive a large-bore, 16 or 18 G, PIVC due to concerns about potential obstetric hemorrhage. Insertion of large-bore PIVCs can be very painful, especially when inserted in the back of the hand or wrist. This current study aimed to assess the necessity of large bore PIVCs in laboring parturients by inquiring about: any existing evidence supporting the practice; how common this practice is in Australia; the proportion of inserted PIVCs that are 18 G or larger; and the number of women requiring blood products in the peripartum period.